The strategy used by the English Study Program MBKM Team to improve the soft skills of students participating in the MBKM program - Nilma Taula’bi’; Elim Trika Sudarsi; Markus Deli Girik Allo (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
In the increasingly rapid development of the times, the development of hard skills and soft skills competencies plays an important role for every student in preparing themselves for the changing times. The purpose of this study is to investigate the strategies used by the PBI MBKM Team to improve the soft skills of students participating in the MBKM program in English Study Program, FKIP, UKI Toraja. This study applies qualitative methods. The subjects of this study are people who are able to become informants to provide information in accordance with the objectives of this study. The informants in this study were the MBKM Team and students who were participating in MBKM program in the English Language Education Study Program UKI Toraja. In accordance with the purpose of this study, the data were collected through observation and interviews. The data analyzed through transcription and coding analysis, while the interview results will be analyzed using thematic analysis. The result of this study confirms that the strategies used by the MBKM Team to improve the soft skills of students participating in the MBKM program are apply active learning, assign group tasks, hold seminars or workshops, provide mentorship, increased digital literacy, and provide constructive feedback.